Imaging Recommendations for Diagnosis, Staging, and Management of Ovarian and Fallopian Tube Cancers - Rupa, Renganathan; Prema, Renganathan; Popat, Palak Bhavesh; Manchanda, Smita; Venkatesh, Kasi; Chandramohan, Anuradha; Subbian, Anbukkani; Rangarajan, Bharath (Indian Journal of Medical and Paediatric Oncology, 2023)
Ovarian malignancy the third most common gynecological malignancy and is the leading cause of death in women. Non-specific clinical presentation delays the diagnosis, and they often present in the advanced stage of disease. No imaging modality is recommended for screening as there is no significant mortality reduction. Ultrasound (USG) is usually the initial modality in suspected ovarian mass. MRI is recommended for the characterization of indeterminate ovarian or adnexal mass on USG. CT abdomen and pelvis with oral and IV contrast is the recommended imaging modality in staging the disease, predicting the resectability and in selecting the patients who would benefit from neoadjuvant chemotherapy. Early ovarian cancers are staged by post-surgical histology and undergo upfront surgery. Advanced disease benefit by neoadjuvant chemotherapy and less morbidity by interval cytoreduction where image-guided biopsy is performed for histological diagnosis. Follow-up recommendations are based on tumor histology. CT/PET CT is recommended for diagnosing recurrence.
Keywords: screening; CT; staging; resectability; cytoreduction; follow-up; PET CT